Situated universals (visions from the Third World) - Marey, Macarena (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This note is a version of an online talk I gave at the Workshop “Kant and Universalism from a Global Perspective”, October 25th 2024, Berlin-Brandenburgische Akademie der Wissenschaften. The event was organised by Marcus WIllaschek and Simon Rebohm. I took the chance to talk about the meaning of reading Kant in the Third World and my experience with the geopolitics of knowledge.